O auto do Bumba-meu-boi do Maranhão e a Lei n. 11.645/2008: contribuições didáticas - Denise Maria Soares Lima; Marcelo Nicomedes dos Reis Silva Filho (EccoS – Revista Científica)
This article aims to provide general educational contributions for art teachers from elementary school, having as background the guidance of Federal Law. 11.645/2008, which deals with the teaching of Afro-Brazilian and Indian history. Specifically it aims: (1) to contextualize the law, (2) to demonstrate the contribution, participation and history of ways of being, living and thinking of black culture in the State of Maranhão expressed in the popular culture, such as Bumba-meu-boi, (3) to provide inputs to strengthen the teaching activity, providing a positive redirection in ethnic-racial relations. The methodology included a literature and field research developed in the communities in the State of Maranhão. Didactically, the paper is organized into four phases: (a) introduction, (b) legislation that brings regulatory aspects and features the Law 10.639/2003 (c) the history of Bumba-meu-boi, the relationship between cultural expressions, the teaching of art education and its application to teaching and (d) closing remarks.